2011
DOI: 10.1177/070674371105600907
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Efficacy of Pregabalin in the Treatment of Generalized Anxiety Disorder

Abstract: Objective: Generalized anxiety disorder (GAD) is a chronic anxiety disorder that leads to significant functional impairment and reduced quality of life. Pregabalin is a novel analogue of the inhibitory neurotransmitter gamma amino butyric acid, which has been proposed as a treatment for a range of conditions including GAD. This study examined the efficacy of pregabalin for GAD across published trials, using a meta-analytic method.Method: This study examined the 7 published placebo-controlled trials of GAD usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…A meta-analysis of 7 placebo-controlled trials of pregabalin for the treatment of generalized anxiety disorder found the overall effect of pregabalin to be significant but small, with a Hedges' g of 0.364, and similarly small for psychic anxiety symptoms (0.349) and somatic anxiety symptoms (0.239) [107]. Using a Bayesian meta-analytic approach, Baldwin et al evaluated the comparative efficacy and tolerability of several drugs for the treatment of GAD, including SSRIs, SNRIs, lorazepam, pregabalin and tiagabine [108].…”
Section: Generalized Anxiety Disordermentioning
confidence: 95%
“…A meta-analysis of 7 placebo-controlled trials of pregabalin for the treatment of generalized anxiety disorder found the overall effect of pregabalin to be significant but small, with a Hedges' g of 0.364, and similarly small for psychic anxiety symptoms (0.349) and somatic anxiety symptoms (0.239) [107]. Using a Bayesian meta-analytic approach, Baldwin et al evaluated the comparative efficacy and tolerability of several drugs for the treatment of GAD, including SSRIs, SNRIs, lorazepam, pregabalin and tiagabine [108].…”
Section: Generalized Anxiety Disordermentioning
confidence: 95%
“…Pregabalin use is becoming widespread in psychiatry and addiction-related treatments. Evidence derived from different studies suggests that pregabalin is an efficacious therapy for GAD [35] and social anxiety disorder [36], with some preliminary evidence for its efficacy in relapse prevention. It is also used as adjunctive therapy in many other psychiatric conditions, such as obsessive compulsive disorder [37], post-traumatic stress disorder, schizophrenia, bipolar mania [38], and major depression [39].…”
Section: Introductionmentioning
confidence: 99%
“…Although pregabalin has demonstrated a significant advantage over placebo in treating GAD in adults, the effect sizes demonstrated to date are small to moderate and psychic symptoms show a greater improvement compared with somatic anxiety symptoms. In contrast, our study found that somatic symptoms seem to improve more (Boschen, 2011). In addition, most studies only evaluate the initial phase of treatment (6-8 weeks), whereas GAD is generally regarded as a long-term condition requiring long-term treatment.…”
Section: Discussionmentioning
confidence: 99%